Exergy analysis of a coupled transcritical and subcritical organic Rankine cycle system for waste heat recovery. (2016) - Gong, Xi-Wu; Wang, Xiao-Qiong; Li, You-Rong
This paper presents a detailed exergy analysis for a novel coupled organic Rankine cycle (CORC) system driven by the waste heat of the flue gas, which combined a transcritical organic Rankine cycle (TORC) with a subcritical organic Rankine cycle (SORC). The results show that the exergy efficiency of the CORC increases with the increase of the inlet pressure of the TORC expander and the decrease of the pinch point temperature difference of the internal heat exchanger. However, the increase of the flue gas temperatures at the inlet and outlet of the evaporator has negative effects. The CORC using isentropic working fluids exhibits better performance than that using dry working fluids. Furthermore, high critical temperature of the working fluid can improve the exergy efficiency. The exergy loss is mainly distributed in the heat exchangers and the expanders, which is different from the result in the traditional TORC.